Mini-Review: Mixed Ionic–Electronic Charge Carrier Localization and Transport in Hybrid Organic–Inorganic Nanomaterials - Romero, Mariano; Mombrú, Dominique; Pignanelli, Fernando; Faccio, Ricardo; Mombrú, Alvaro W. (Frontiers in Chemistry, 2020)
In this mini-review, a comprehensive discussion on the state-of-the-art of hybrid organic-inorganic mixed ionic-electronic conductors (hOI-MIECs) is given, focusing in conducting polymer nanocomposites comprising inorganic nanoparticles ranging from ceramic-in-polymer to polymer-in-ceramic concentration regimes. First, a brief discussion on fundamental aspects of mixed ionic-electronic transport phenomena considering the charge carrier transport at bulk regions together with the effect of the organic-inorganic interphase of hybrid nanocomposites is presented. We also make a recount of updated instrumentation techniques to characterize structure, microstructure, chemical composition and mixed ionic-electronic transport with special focus on those relevant for hOI-MIECs. Raman imaging and impedance spectroscopy instrumentation techniques are particularly discussed as relatively simple and versatile tools to study the charge carrier localization and transport at different regions of hOI-MIECs including both bulk and interphase regions to shed some light on the mixed ionic-electronic transport mechanism. In addition, we will also refer to different device assembly configurations and in-situ/operando measurements experiments to analyze mixed ionic-electronic conduction phenomena for different specific applications. Finally, we will also review the broad range of promising applications of hOI-MIECs, mainly in the field of energy storage and conversion, but also in the emerging field of electronics and bio-electronics.